Thymoma surgery: extreme surgical indications - Novellis, Pierluigi; Veronesi, Giulia; Raffeeq, Zaheer; Alloisio, Marco (Journal of Thoracic Disease, 2019)
Complete resection for thymoma is the most remarkable prognostic factors in thymic tumours (1,2). At initial stages, a complete and radical resection could easily be achieved with an excellent prognosis. Tumours invading lungs, great vessels or pericardium have a higher rate of R1 to R2 resection and higher risk of recurrence, and therefore, a worse prognosis can be observed (3). In locally advanced thymus tumors some factors must be kept in close observation including: local extension to large mediastinal vessels; innominate vein, superior vena cava (SVC) and pulmonary vessels, infiltration of the pericardium and distant metastases to the pleura and organ within it with or without pleural diffusion.